Fundamentals of Sliding-Mode Control Design - Kunusch, Cristian (2012)
This chapter provides an introduction to Variable Structure Control theory and its extension to the so-called Sliding-Mode (SM) control. The presentation is not intended as a comprehensive survey of the state-of-the-art in the field, but to supply the basic concepts on SM control required to understand the developments to come in this book. The readers can use this material as a straightforward introduction to the field of SM control.